Mixed symmetric duality in nondifferentiable mathematical programming - Yang, X.; Teo, Kok Lay; Yang, X. (Scientific Publishers, 2003)
A mixed symmetric dual formulation is presented for a class of nondifferentiable nonlinear programming problems with multiple arguments. Weak, strong and converse duality theorems are established. The mixed symmetric dual formulation unifies the two existing symmetric dual formulations in the literature.